Prevalence of self-medication among students of State University of Amazonas (Brazil) - Iuras, Anderson; Franco Marques, Andre Augusto; Roberti Garcia, Lucas da Fonseca [UNESP]; Santiago, Michael Brian; Lima Santana, Luana Kelly (Spemd-soc Portuguesa Estomatologia & Medicina Dentaria, 2016)
Objective: Brazil occupies the fifth position in the list of medical drugs consumption, being first in Latin America. The present study aimed to determine whether this practice is common among students of the State University of Amazonas (Brazil). Methods: Students from the nursing, medicine and dentistry courses; and attending the third, fourth and fifth semesters were submitted to questionnaires to assess the prevalence of self-medication. However, from the students previously selected, only one hundred-eighty completely attended to the inclusion criteria. Results: When asked if they have already used non-prescription drugs, 89% of the students answered yes, and only 11% answered no. Headache, muscle aches, sore throat, fever, and inflammation were the main complaints that led to the practice of self-medication. Analgesics/antipyretics, anti-inflammatories, antibiotics and muscle relaxants represented the main classes of drugs used to alleviate such symptoms and signs. Conclusion: Preventive and educational measures should be applied, contributing to the reduction of risks caused by self-medication; and consequently, educating future professionals regarding the danger that some medical drugs may represent. (C) 2016 Sociedade Portuguesa de Estomatologia e Medicina Dentaria. Published by Elsevier Espana, S.L.U.
Keywords: Self medication; Adverse effects; Therapeutic use